Kinetic studies and performance analysis of Indonesian rice husk pyrolysis. Issue 1 (April 2021) - Kasmiarno, L D; Steven, S; Rizkiana, J; Restiawaty, E; Bindar, Y
Abstract: Rice husk is abundantly available biomass in Indonesia and it can be a potential source of high-value energy source. In the present work, pyrolysis of rice husk was subjected to various temperature and used as a method to produce bio-oil. The decomposition profile of rice was examined at different heating rates (10, 20, 30, and 40°C/min) using a thermogravimetric analysis (TGA) method. The pyrolysis kinetics were evaluated using three different kinetic models: Kissinger-Akahira-Sunose (KAS), Ozawa-Flynn-Wall (OFW), and Coats-Redfern (CR). The activation energy for KAS, OFW, and CR was centered at 251.62 kJ/mol, 253.32 kJ/mol, and 33.92 kJ/mol, respectively. Varying activation energy with conversion was observed, which reveals that the pyrolysis of rice husk processes through complex reaction. The production of bio-oil from rice husk using pyrolysis method was studied at different temperature conditions (300, 400, 500, 600°C). Results showed that bio-oil and gas products increase at higher temperature. The highest yield of bio-oil was produced at 600°C with 46.3 grams (37%-wt). The specific test showed that the density, viscosity, and acid value of bio-oil decreased at higher temperatures indicating that different pyrolysis conditions might lead to the different bio-oil quality.